3D Flake‐Like Bi2Te3 with Outstanding Lightweight Electromagnetic Wave Absorption Feature. (23rd February 2018) - Chen, Jiabin; Liang, Xiaohui; Quan, Bin; Yang, Zhihong; Du, Youwei; Ji, Guangbin
Abstract: Flake‐like semiconductors with strong interfacial polarization exhibit excellent electromagnetic absorption properties. To the best of the knowledge, 3D flake‐like Bi2 Te3 is never reported as effective MAMs (microwave absorption materials). Herein, it is first introduced the novel lightweight microwave absorption of 3D flake‐like Bi2 Te3 synthesized by a simple hydrothermal process. Compared with the traditional research objects, the obtained Bi2 Te3 possessed prominent absorbing ability at a rather thin thickness (1.0 mm), which will draw much attention to new‐materials for electromagnetic wave absorption. Abstract : 3D flake‐like Bi2 Te3 is first designed as a novel lightweight microwave absorbing material by a simple hydrothermal progress. Its outstanding lightweight electromagnetic wave absorption feature makes Bi2 Te3 to be a promising candidate for traditional electromagnetic absorbents.